THE CORRELATION OF ISLAM-CHRISTIAN TO FIGHT RACISM (AN ANALYSIS OF CONFLICT AND RELIGIOUS MODERATION IN POSO) - Mukramin, Sam'un; Meiyani, Eliza; Ismail, Lukman; Nursida, Andi (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2021)
Islam and Christian have a concept of religious moderation as a philosophy of belief and guidelines to behave towards followers of other religions that always maintain balance. The existence of Racism, conflict, and violence in the name of religion occurred in Poso, Central Sulawesi is the result of the misinterpretation of verses in the holy book which puts forward individualistic attitudes ego, and extremist thinking. This research was descriptive qualitative with a case study approach. The informants were selected by using the purposive sampling technique and collecting data by reviewing through observation, interviews, and documentation. The research findings showed that religious moderation was essential to be carried out through a) preventive efforts to fight Racism comprehensively, it is not exclusively perceived as a difference, b) values and norms which its essence of maintaining dignity and protecting human life as God's creatures, c) socio-cultural capital and basic principles in building relations between religious adherents, d) strengthening the nation with religious values, Pancasila values, cultural values, human values, washatiyah values, and scientific values and e) massive and measurable socialization of religious moderation with a wisdom approach local people to have an understanding and an alumsuth perspective.الملخصفي الأساس ، لدى كل من الإسلام والمسيحية مفهوم الاعتدال الديني كفلسفة إيمانية ومبادئ توجيهية للسلوك تجاه أتباع الديانات الأخرى الذين يحافظون دائمًا على التوازن. إن وجود العنصرية والصراع والعنف باسم الدين الذي حدث في بوسو ، وسط سولاويزي ، نتيجة سوء تفسير الآيات في الكتاب المقدس ، يطرح مواقف الأنا الفردية والتفكير المتطرف. يعتبر هذا البحث نوعيًا وصفيًا مع منهج دراسة الحالة ، حيث يتم اختيار المخبرين عن طريق أخذ العينات الهادف من خلال الفحص من خلال الملاحظات والمقابلات والتوثيق. تظهر نتائج الدراسة أن الاعتدال الديني مهم للغاية ليتم تنفيذه من خلال: أ) الجهود الوقائية لمكافحة العنصرية بشكل شامل ، وليس حصريًا في عرض الاختلاف ، ب) القيم والأعراف التي يتمثل جوهرها في الحفاظ على الكرامة وحماية الإنسان الحياة كمخلوقات الله ، ج) رأس المال الاجتماعي والثقافي والمبادئ الأساسية في بناء العلاقات بين أتباع الديانات ، د) تقوية الأمة بالقيم الدينية وقيم البانتشاسيلا والقيم الثقافية والقيم الإنسانية وقيموالقيم الوشاطيةالعلمية و هـ) التنشئة الاجتماعية الهائلة والقابلة للقياس للاعتدال الديني مع نهج الحكمة للسكان المحليين بحيث يكون لديهم منظور وفهم مرعب.